Chronic glucokinase activator treatment activates liver Carbohydrate response element binding protein and improves hepatocyte ATP homeostasis during substrate challenge. Issue 11 (7th July 2020) - Ford, Brian E.; Chachra, Shruti S.; Alshawi, Ahmed; Brennan, Alfie; Harnor, Suzannah; Cano, Celine; Baker, David J.; Smith, David M.; Fairclough, Rebecca J.; Agius, Loranne
Abstract: Aim: To test the hypothesis that glucokinase activators (GKAs) induce hepatic adaptations that alter intra‐hepatocyte metabolite homeostasis. Methods: C57BL/6 mice on a standard rodent diet were treated with a GKA (AZD1656) acutely or chronically. Hepatocytes were isolated from the mice after 4 or 8 weeks of treatment for analysis of cellular metabolites and gene expression in response to substrate challenge. Results: Acute exposure of mice to AZD1656 or a liver‐selective GKA (PF‐04991532), before a glucose tolerance test, or challenge of mouse hepatocytes with GKAs ex vivo induced various Carbohydrate response element binding protein (ChREBP) target genes, including Carbohydrate response element binding protein beta isoform (ChREBP‐β), Gckr and G6pc . Both glucokinase activation and ChREBP target gene induction by PF‐04991532 were dependent on the chirality of the molecule, confirming a mechanism linked to glucokinase activation. Hepatocytes from mice treated with AZD1656 for 4 or 8 weeks had lower basal glucose 6‐phosphate levels and improved ATP homeostasis during high substrate challenge. They also had raised basal ChREBP‐β mRNA and AMPK‐α mRNA ( Prkaa1, Prkaa2 ) and progressively attenuated substrate induction of some ChREBP target genes and Prkaa1 and Prkaa2 . Conclusions: Chronic GKA treatment of C57BL/6 mice for 8 weeks activates liver ChREBP and improves the resilience of hepatocytes to compromised ATP homeostasis during high‐substrate challenge. These changes are associated with raised mRNA levels of ChREBP‐β and both catalytic subunits of AMP‐activated protein kinase.